Public Opinion and Public Policy: Heroin and Other Opioids. (October 2019) - Cook, Amy Kyle; Brownstein, Henry H.
Virginia, much like other states, has experienced unprecedented rates of heroin and prescription opioid abuse, overdoses, and deaths. Given the wide range of competing voices concerning drug policy and the complicated situation of the contemporary opioid epidemic, this study examines whether public opinion is reflected in public policy toward illicit involvement with opioids. The 2016 Commonwealth Public Policy Survey, a statewide representative sample of 1, 000 Virginia residents, found that Virginians are supportive of treatment over arrest for heroin and prescription pill abusers and factors such as race, education, and political affiliation are predictive of support for treatment over arrest. More importantly, the results of this poll converge with legislative policies of the 2017 General Assembly, supporting the notion that public support can have an influence on the policymaking process. Policy implications are discussed.